“Some They Need Male, Some They Need Female”: A Gendered Approach for Breast Cancer Detection in Uganda - Ikhile, Deborah; Omodara, Damilola; Seymour-Smith, Sarah; Musoke, David; Gibson, Linda (Frontiers in Global Women's Health, 2022)
Introduction There are several challenges associated with breast cancer detection in Uganda and other low-and-middle-income countries. One of the identified challenges is attributed to the health workers' gender, which facilitates gender disparities in access to breast cancer detection services. Although this challenge is well acknowledged in existing literature, there are hardly any studies on how it can be addressed. Therefore, drawing on an intersectionality lens, our study examined how to address gender disparities facilitated by health workers' gender in accessing breast cancer detection services in Uganda. Materials and Methods We collected qualitative data through semi-structured interviews with twenty participants comprising community health workers, primary health care practitioners, non-governmental organizations, district health team, and the Ministry of Health. For the data analysis, thematic analysis was conducted on NVivo using Braun and Clarke's non-linear 6-step process to identify the themes presented in the results section. Results Four themes emerged from the data analysis: understanding a woman's gender constructions; health workers' approachability; focus on professionalism, not sex; and change in organizational culture. These themes revealed participants' perceptions regarding how to address gender disparities relating to the role health workers' gender play in breast cancer detection. Through the intersectionality lens, our findings showed how gender intersects with other social stratifiers such as religious beliefs, familial control, health worker's approachability, and professionalism within the health workforce. Conclusion Our findings show that the solutions to address gender disparities in breast cancer detection are individually and socially constructed. As such, we recommend a gendered approach to understand and redress the underlying power relations perpetuating such constructions. We conclude that taking a gendered approach will ensure that breast cancer detection programs are context-appropriate, cognizant of the prevailing cultural norms, and do not restrict women's access to breast cancer detection services.